Женщина из шелкового мира: [роман] / А. Берсенева - Берсенева Анна (Русский характер, 2015)
Экземпляры: ХР (20181211) / Инвентарный номер: 45289 / Цена: 118 / Сис.шифр: Р 2 / Авт.знак: Б 51 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44